2018
DOI: 10.1039/c7cp07896j
|View full text |Cite
|
Sign up to set email alerts
|

High-performance thermoelectric materials based on ternary TiO2/CNT/PANI composites

Abstract: In the present work, we report the fabrication of high-performance thermoelectric materials using TiO2/CNT/PANI ternary composites. We showed that a conductivity of ∼2730 S cm-1 can be achieved for the binary CNT (70%)/PANI (30%) composite, which is the highest recorded value for the reported CNT/PANI composites. We further demonstrated that the Seebeck coefficient of CNT/PANI composites could be enhanced by incorporating TiO2 nanoparticles into the binary CNT/PANI composites, which could be attributed to lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 62 publications
0
30
0
Order By: Relevance
“…The semiconducting CNTs with band gaps have much higher S values than metallic CNTs. Energy filtering effects of the CNT-based composites have been reported. However, the origin with detailed experimental evidence has not been discussed. Recently, Hsu and Yu reported the energy filtering effect at the junction between PEDOT and CNTs, where only semiconducting CNTs contribute to the energy filtering .…”
Section: Resultsmentioning
confidence: 99%
“…The semiconducting CNTs with band gaps have much higher S values than metallic CNTs. Energy filtering effects of the CNT-based composites have been reported. However, the origin with detailed experimental evidence has not been discussed. Recently, Hsu and Yu reported the energy filtering effect at the junction between PEDOT and CNTs, where only semiconducting CNTs contribute to the energy filtering .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, for a pair of 5 legs, the generated maximal power density was 650 nW cm À2 at a DT of 50 K. Even, after 1000 bending cycles, the performance of the device remained unaltered. Erden et al 158 reported a ternary hybrid nanocomposite of TiO 2 /CNT/PANI, where the Seebeck coefficient of the binary CNT/PANI composite could be increased by integrating TiO 2 nanoparticles into it. The ternary nanocomposites provided two interfaces of TiO 2 /a-CNT and TiO 2 /PANI for the scattering of low energy carriers, which helped in lowering the thermal conductivity and increasing the thermopower of the composite.…”
Section: Materials Advances Reviewmentioning
confidence: 99%
“…Orientation via rubbing 9.4 220 000 2000 Vijayakumar et al [83] P3HT Stretching of polymer chains 112 13 16 Hynynen et al [84] PANI A-CNT Sulfonic acid Interlayer 2012 401 Li et al [85] PANI SWCNT Percolation threshold 12 4000 100 Wu et al [86] PANI Graphene PDG Growth from graphene 604 14.5 0.22 0.74 Lin et al [87] PANI SWCNT π−π stacking 50 375 98.5 Wang et al [88] PANI MoS 2 MoS 2 between PANI layers 5.3 2.5 0.007 Mombrú et al [89] PANI SWCNT Ammonia Dedoping 35 2400 345 9 mV 1.1 µW Li et al [90] PANI:PSS Ag NW 380 0.16 0.85 Du et al [92] PANI CNT, TiO 2 Energy filtering effect 18 2733 114 Erden et al [93] PANI SnSeS, PVDF PANI-SnSeS network 370 10 134 Ju et al [94] PANI Bi 2 Se 3 2D VRH 188 30 0.25 107 0.18 Mitra et al [95] PANI Te NR Annealing 170 20 54 Wang et al [96]…”
Section: (22 Of 26)mentioning
confidence: 99%
“…More advanced strategies include the use of double doping, that is, the creation of ternary systems, where two fillers can be added into a single polymer matrix. In the work by Erden and co‐workers, [ 93 ] the combined effect of amine‐functionalized CNTs (a‐CNT) and TiO 2 nanoparticle doping is studied on the TE performance of PANI. Incorporation of a‐CNT at 70 wt% into the matrix led to a significant increase of electrical conductivity up to 2733 S cm −1 and Seebeck coefficient up to ≈18 µV K −1 .…”
Section: Panimentioning
confidence: 99%